A graphite negative electrode material and preparation method thereof and battery
By building a crosslinking network in graphite negative electrode material, the problem of unstable structure during charging and discharging of graphite materials is solved, and the capacity stability and cycling performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202411521965.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The structure of graphite negative electrode material is unstable during charging and discharging, and the laminate is prone to fall off and rupture, affecting the performance and life of the battery.
By reacting expanded graphite with zinc chloride, phytic acid and ethyl orthosilicate, a cross-linking network is built to protect the internal structure of graphite and improve the stability of the material.
It effectively avoids structural changes in graphite materials during charging and discharging, improves the capacity stability and cycling performance of the battery, and extends the service life of the battery.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for new energy batteries, and in particular to a graphite negative electrode material and a preparation method thereof and a battery. Background Art
[0002] With the continuous development of new energy vehicles, energy storage and other industries, the new energy battery industry has been continuously upgraded, and the requirements for battery charging and discharging performance and energy density have also been continuously improved. As one of the four key materials of the battery, the negative electrode material has a significant impact on the battery's energy density, cycle performance, charge and discharge rate, and low-temperature discharge performance. Graphite is the most widely used and most commercially used negative electrode material. This is mainly because graphite has a relatively high capacity and conductivity, and it is cheap and easy to obtain.
[0003] Only by continuously improving the performance and technical level of negative electrode materials can we promote the progress and development of battery technology and meet higher-demand application scenarios. The graphite interlayer is not only a storage space for lithium ions, but also a solid-phase diffusion channel for lithium ions. If the interlayer spacing of graphite is increased, not only can the capacity of the material be increased, but also the rate charging and discharging performance of the material can be improved. In order to improve the capacity and rate increase of graphite negative electrodes, graphite is usually expanded when preparing graphite negative electrode materials to expand the graphite interlayer spacing. However, the interlayer bonding force of graphite itself is poor, resulting in an unstable structure, and it is easy to co-insert solvent molecules, causing the layers to fall off and break during the charging and discharging process. This problem is more serious for graphite after expansion treatment.
[0004] To this end, existing technical improvements usually use asphalt and other substances to wrap the outer surface of graphite to limit the volume expansion of graphite materials during charging and discharging. This method also has many defects. For example, it is difficult for macromolecular substances such as asphalt to penetrate into the interior of graphite and cannot effectively protect the internal structure. Expanded graphite has a rich layer of curled flake graphite inside. When the battery is charged and discharged too many times, the expanded graphite may partially decompose, reorganize and change its structure. These changes will have a significant impact on the performance of the battery, such as capacity decay. Summary of the invention
[0005] In order to solve the problems mentioned in the background technology, the present invention provides a method for preparing a graphite negative electrode material, by reacting expanded graphite with a series of substances that are easy to penetrate into the expanded graphite, such as zinc chloride, phytic acid and ethyl orthosilicate, to construct a cross-linked network between graphite layers inside the expanded graphite, effectively protect the internal structure of the expanded graphite, and improve the stability of the expanded graphite.
[0006] Specifically:
[0007] A method for preparing a graphite negative electrode material, comprising the steps of:
[0008] Step 1, adding expanded graphite to a zinc chloride solution, and then adding sodium dodecylbenzene sulfonate, heating and stirring, after the stirring is completed, filtering the reaction mixture to separate the zinc-containing graphite material, washing and drying it for later use;
[0009] Step 2: adding the zinc-containing graphite material obtained in step 1 to the phytic acid solution, heating and stirring, filtering the reacted material after stirring, separating the graphite solid, washing and drying it for later use;
[0010] Step 3: Add the graphite solid obtained in step 2 to the ethyl orthosilicate solution, heat and stir, and after stirring, filter the reacted product to separate the solid product, wash and dry to obtain the graphite negative electrode material.
[0011] Furthermore, in step 1, the zinc chloride solution is prepared by mixing zinc chloride with deionized water to prepare a solution with a concentration of 0.1 to 1 mol / L; the mass ratio of expanded graphite to zinc chloride solution is 1:5 to 20; and sodium dodecylbenzene sulfonate is added at 1% to 5% of the mass of the expanded graphite.
[0012] Furthermore, in step 1, a magnetic stirrer is used for stirring; the stirring temperature is 40-80° C., the stirring speed is 200-500 rpm, and the stirring time is 6-12 h.
[0013] Furthermore, in step 2, the phytic acid solution is prepared by mixing phytic acid powder with deionized water to prepare a solution with a concentration of 0.5 to 0.8 mol / L; the mass ratio of the zinc-containing graphite material to the phytic acid solution is 1:40 to 50.
[0014] Furthermore, in step 2, a magnetic stirrer is used for stirring; the stirring temperature is 40-60° C., the stirring speed is 200-300 rpm, and the stirring time is 12-24 h.
[0015] Furthermore, in step three, the tetraethyl orthosilicate solution is prepared by mixing tetraethyl orthosilicate and ethanol in a volume ratio of 1:3 to 5; the mass ratio of graphite solid to tetraethyl orthosilicate solution is 1:30 to 50.
[0016] Furthermore, in step three, a magnetic stirrer is used for stirring; the stirring temperature is 30-50° C., the stirring speed is 300-350 rpm, and the stirring time is 6-8 h.
[0017] Furthermore, in step three, the solid product is washed with deionization for 5 to 8 times; the drying temperature is 60 to 100° C., and the drying time is 2 to 4 hours.
[0018] In addition, the present invention also provides a graphite negative electrode material, which is prepared by the above-mentioned method for preparing the graphite negative electrode material.
[0019] In addition, the present invention also provides a battery, the negative electrode material of which is prepared by the above-mentioned method for preparing the graphite negative electrode material.
[0020] Compared with the prior art, the present invention has the following beneficial features:
[0021] 1. The preparation method of the graphite negative electrode material of the present invention comprises the following steps: firstly immersing the graphite material in a solution containing zinc ions, so that the zinc ions enter the surface and the internal interlayer structure of the graphite by diffusion, and then fixing the zinc ions on the graphite layer by drying, heat treatment and other processes; then immersing the graphite material in a phytic acid solution, wherein the phytic acid molecule contains a plurality of phosphate groups, and the zinc element can form a stable complex structure with the phosphate groups in the phytic acid, and the graphite layer is doped with a plurality of zinc element sites, so that the phytic acid is cross-linked with the adjacent zinc elements, and finally a cross-linked network is formed between the graphite layers; finally, immersing the graphite material in a positive electrode solution, wherein the phytic acid molecule contains a plurality of phosphate groups, and the zinc element can form a stable complex structure with the phosphate groups in the phytic acid, and the graphite layer is doped with a plurality of zinc element sites, so that the phytic acid is cross-linked with the adjacent zinc elements, and finally a cross-linked network is formed between the graphite layers; Ethyl silicate solution causes ethyl orthosilicate to hydrolyze. The silicon dioxide produced by hydrolysis can fix the zinc sites on the graphite layer, making the combination of zinc and graphite more stable. At the same time, silicon dioxide can also combine with the functional groups of phytic acid to fix silicon dioxide on the surface of the cross-linked network. Each component of this system is a substance that can easily penetrate into the interior of graphite. Through the synergistic effect of each component, a cross-linked network is constructed between the layers inside and outside the graphite, thereby improving the stability of the graphite material and avoiding defects such as partial decomposition, reorganization and structural changes of the internal structure of the graphite material under the influence of stress after multiple charge and discharge.
[0022] 2. The preparation method of the graphite negative electrode material of the present invention, the silicon dioxide on the cross-linked structure can not only enhance the structural stability, but also after being applied to the battery, the silicon dioxide can provide embedding and detachment sites for lithium ions, thereby improving the performance of the battery, and the battery has high capacity.
[0023] 3. The preparation method of the graphite negative electrode material of the present invention, the zinc element in the system can act as a Lewis acid, in the hydrolysis reaction of ethyl orthosilicate, the zinc ion can interact with water or hydroxyl groups, so that the electron cloud in the water or hydroxyl groups is shifted, thereby enhancing the nucleophilicity of the hydroxyl groups, and the hydroxyl groups with enhanced nucleophilicity are more likely to attack the silicon atoms in the ethyl orthosilicate molecules, prompting the ethoxy groups to be replaced by hydroxyl groups, thereby accelerating the hydrolysis reaction of ethyl silicate; at the same time, the phosphate groups rich in phytic acid can release protons, increase the hydrogen ion concentration in the reaction system, thereby playing a role similar to that of an acid catalyst, accelerating the hydrolysis of ethyl orthosilicate.
[0024] 4. The graphite negative electrode material obtained by the method for preparing the graphite negative electrode material of the present invention is applied to batteries. The prepared battery has a stable capacity after long-term charge and discharge without the defect of excessively rapid attenuation. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] In order to facilitate those skilled in the art to implement the present invention, some of the reagents used in the embodiments and comparative examples are now described:
[0027] Expanded graphite: Qingdao Hexinda Carbon Materials;
[0028] Zinc chloride: Jinan Jibin Chemical, analytical grade;
[0029] Phytic acid: Shandong Chengtai Chemical, analytical grade;
[0030] Tetraethyl orthosilicate: Shandong Taixi Chemical Industry;
[0031] Ethanol: Jinan Huiteng Chemical;
[0032] Sodium dodecylbenzenesulfonate: Nanjing Milan Chemical.
[0033] Example 1
[0034] A method for preparing a graphite negative electrode material, comprising the steps of:
[0035] S1. Prepare zinc chloride solution: mix zinc chloride and deionized water to prepare a solution with a concentration of 1 mol / L;
[0036] S2, zinc doping: add expanded graphite to the zinc chloride solution, the mass ratio of expanded graphite to zinc chloride solution is 1:20; then add sodium dodecylbenzene sulfonate, the sodium dodecylbenzene sulfonate is added according to 5% of the mass of expanded graphite; place the reaction vessel in a magnetic stirrer, raise the temperature to 40°C, set the stirring speed to 200rpm, stir for 12h, after stirring, filter the reacted mixed solution to separate the zinc-containing graphite material, wash the filtered zinc-containing graphite material 3 times with deionized water to remove unabsorbed zinc ions and other impurities, dry in an oven at 80°C for 12h, thoroughly remove moisture, and set aside;
[0037] S3, preparing phytic acid solution: mixing phytic acid powder with deionized water to prepare a solution with a concentration of 0.8 mol / L;
[0038] S4, cross-linking: adding zinc-containing graphite material to the phytic acid solution, the mass ratio of zinc-containing graphite material to phytic acid solution is 1:50; placing the reaction vessel in a magnetic stirrer, raising the temperature to 40 ° C, setting the stirring speed to 200 rpm, stirring for 24 hours, after the stirring is completed, the reaction mixture is filtered to separate the graphite solid, and the filtered graphite solid is washed with deionized water to remove unreacted phytic acid and other impurities, and dried in an oven at 60 ° C for 12 hours to completely remove moisture for standby use;
[0039] S5. Prepare a tetraethyl orthosilicate solution: mix tetraethyl orthosilicate and ethanol in a volume ratio of 1:5;
[0040] S6. Fixation enhancement: add graphite solid to the ethyl orthosilicate solution, the mass ratio of graphite solid to ethyl orthosilicate solution is 1:50; place the reaction container on a magnetic stirrer, raise the temperature to 30°C, set the stirring speed to 300 rpm, and stir for 8 hours. After the stirring is completed, filter the reaction mixture to separate the solid product, wash the filtered solid product 5 times with deionized water to remove unreacted phytic acid and other impurities, and dry it in an oven at 60°C for 4 hours to completely remove moisture to obtain a graphite negative electrode material.
[0041] Example 2
[0042] A method for preparing a graphite negative electrode material, comprising the steps of:
[0043] S1. Prepare zinc chloride solution: mix zinc chloride and deionized water to prepare a solution with a concentration of 0.1 mol / L;
[0044] S2, zinc doping: add expanded graphite to the zinc chloride solution, the mass ratio of expanded graphite to zinc chloride solution is 1:5; then add sodium dodecylbenzene sulfonate, the sodium dodecylbenzene sulfonate is added according to 1% of the mass of expanded graphite; place the reaction vessel in a magnetic stirrer, raise the temperature to 80°C, set the stirring speed to 500rpm, stir for 6h, after stirring, filter the reacted mixed solution to separate the zinc-containing graphite material, wash the filtered zinc-containing graphite material 5 times with deionized water to remove unabsorbed zinc ions and other impurities, dry in an oven at 120°C for 6h, thoroughly remove moisture, and set aside;
[0045] S3, preparing phytic acid solution: mixing phytic acid powder with deionized water to prepare a solution with a concentration of 0.5 mol / L;
[0046] S4, cross-linking: adding zinc-containing graphite material to the phytic acid solution, the mass ratio of zinc-containing graphite material to phytic acid solution is 1:40; placing the reaction vessel on a magnetic stirrer, raising the temperature to 60°C, setting the stirring speed to 300 rpm, stirring for 12 hours, after the stirring is completed, filtering the reaction mixture to separate the graphite solid, washing the filtered graphite solid 5 times with deionized water to remove unreacted phytic acid and other impurities, and drying in an oven at 100°C for 6 hours to completely remove moisture for standby use;
[0047] S5. Prepare a tetraethyl orthosilicate solution: mix tetraethyl orthosilicate and ethanol in a volume ratio of 1:3;
[0048] S6. Fixation enhancement: add graphite solid to the ethyl orthosilicate solution, the mass ratio of graphite solid to ethyl orthosilicate solution is 1:30; place the reaction container on a magnetic stirrer, raise the temperature to 50°C, set the stirring speed to 350 rpm, and stir for 6 hours. After the stirring is completed, filter the reaction mixture to separate the solid product, wash the filtered solid product 8 times with deionized water to remove unreacted phytic acid and other impurities, and dry it in an oven at 100°C for 2 hours to completely remove moisture to obtain a graphite negative electrode material.
[0049] Example 3
[0050] A method for preparing a graphite negative electrode material, comprising the steps of:
[0051] S1. Prepare zinc chloride solution: mix zinc chloride and deionized water to prepare a solution with a concentration of 0.5 mol / L;
[0052] S2, zinc doping: add expanded graphite to the zinc chloride solution, the mass ratio of expanded graphite to zinc chloride solution is 1:10; then add sodium dodecylbenzene sulfonate, the sodium dodecylbenzene sulfonate is added according to 3% of the mass of expanded graphite; place the reaction container on a magnetic stirrer, increase the temperature to 60°C, set the stirring speed to 400 rpm, stir for 8 hours, after the stirring is completed, filter the reaction mixture to separate the zinc-containing graphite material, wash the filtered zinc-containing graphite material 4 times with deionized water to remove unabsorbed zinc ions and other impurities, dry in an oven at 100°C for 9 hours, completely remove moisture, and set aside;
[0053] S3, preparing phytic acid solution: mixing phytic acid powder with deionized water to prepare a solution with a concentration of 0.6 mol / L;
[0054] S4, cross-linking: adding zinc-containing graphite material to the phytic acid solution, the mass ratio of zinc-containing graphite material to phytic acid solution is 1:47; placing the reaction vessel in a magnetic stirrer, raising the temperature to 40-50°C, setting the stirring speed to 260rpm, stirring for 15h, after the stirring is completed, the reaction mixture is filtered to separate the graphite solid, and the filtered graphite solid is washed 4 times with deionized water to remove unreacted phytic acid and other impurities, and dried in an oven at 70°C for 9h to completely remove moisture for standby use;
[0055] S5. Prepare a tetraethyl orthosilicate solution: mix tetraethyl orthosilicate and ethanol in a volume ratio of 1:4.5;
[0056] S6. Fixation enhancement: add graphite solid to the ethyl orthosilicate solution, the mass ratio of graphite solid to ethyl orthosilicate solution is 1:40; place the reaction container on a magnetic stirrer, raise the temperature to 40°C, set the stirring speed to 320rpm, and stir for 7 hours. After the stirring is completed, filter the reaction mixture to separate the solid product, wash the filtered solid product 7 times with deionized water to remove unreacted phytic acid and other impurities, and dry it in an oven at 80°C for 3 hours to completely remove moisture to obtain a graphite negative electrode material.
[0057] Comparative Example 1
[0058] A method for preparing a graphite negative electrode material, comprising the steps of:
[0059] S1, mixing phytic acid powder with deionized water to prepare a solution with a concentration of 0.8 mol / L;
[0060] S2, add expanded graphite to the phytic acid solution, the mass ratio of expanded graphite to phytic acid solution is 1:50; the reaction vessel is placed in a magnetic stirrer, the temperature is raised to 40 ° C, the stirring speed is set to 200rpm, and stirred for 24h. After the stirring is completed, the mixed solution after the reaction is filtered to separate the graphite solid, and the filtered graphite solid is washed with deionized water to remove unreacted phytic acid and other impurities, and dried in an oven at 60 ° C for 12h to completely remove moisture for standby use;
[0061] S3, mixing tetraethyl orthosilicate and ethanol in a volume ratio of 1:5;
[0062] S4. Add graphite solid to the ethyl orthosilicate solution, with the mass ratio of graphite solid to ethyl orthosilicate solution being 1:50; place the reaction container on a magnetic stirrer, raise the temperature to 30°C, set the stirring speed to 300 rpm, and stir for 8 hours. After the stirring is completed, filter the reaction mixture to separate the solid product, wash the filtered solid product 5 times with deionized water to remove unreacted phytic acid and other impurities, and dry it in an oven at 60°C for 4 hours to completely remove moisture to obtain a graphite negative electrode material.
[0063] Comparative Example 2
[0064] A method for preparing a graphite negative electrode material, comprising the steps of:
[0065] S1. Prepare zinc chloride solution: mix zinc chloride and deionized water to prepare a solution with a concentration of 1 mol / L;
[0066] S2, zinc doping: add expanded graphite to the zinc chloride solution, the mass ratio of expanded graphite to zinc chloride solution is 1:20; then add sodium dodecylbenzene sulfonate, the sodium dodecylbenzene sulfonate is added according to 5% of the mass of expanded graphite; place the reaction vessel in a magnetic stirrer, raise the temperature to 40°C, set the stirring speed to 200rpm, stir for 12h, after stirring, filter the reacted mixed solution to separate the zinc-containing graphite material, wash the filtered zinc-containing graphite material 3 times with deionized water to remove unabsorbed zinc ions and other impurities, dry in an oven at 80°C for 12h, thoroughly remove moisture, and set aside;
[0067] S3, preparing phytic acid solution: mixing phytic acid powder with deionized water to prepare a solution with a concentration of 0.8 mol / L;
[0068] S4, cross-linking: adding zinc-containing graphite material to the phytic acid solution, the mass ratio of zinc-containing graphite material to phytic acid solution is 1:50; placing the reaction container on a magnetic stirrer, raising the temperature to 40°C, setting the stirring speed to 200 rpm, stirring for 24 hours, after the stirring is completed, filtering the reaction mixture to separate the graphite solid, washing the filtered graphite solid with deionized water to remove unreacted phytic acid and other impurities, and drying in an oven at 60°C for 12 hours to completely remove moisture to obtain a graphite negative electrode material.
[0069] Batteries were prepared and tested according to the following methods for Examples 1-3 and Comparative Examples 1-2:
[0070] According to the mass ratio of 95:1.5:1.5:2, the graphite negative electrode material, conductive agent (SP), CMC and SBR are mixed and coated on copper foil to obtain the negative electrode sheet. According to the mass ratio of 96.5:2:1.5, the positive electrode active material lithium cobalt oxide, conductive agent (SP) and PVDF are mixed evenly and coated on aluminum foil to obtain the positive electrode sheet. The electrolyte is 1mol / L LiPF6+EC+EMC, and the separator is a polyethylene / propylene composite microporous membrane. They are assembled into a battery.
[0071] Cycle test: The electrochemical performance test of each group of batteries was carried out on Wuhan Blue Electric CT2001A battery tester, with a charge and discharge rate of 1C and a charge and discharge voltage range of 3V to 4.35V. The capacity retention rate was tested for 100 weeks, 300 weeks, 600 weeks, and 1000 weeks respectively. The test results are as follows:
[0072] Initial capacity (mAh / g) 100-week capacity retention rate (%) 300-week capacity retention rate (%) 600-week capacity retention rate (%) 1000-week capacity retention rate (%) Example 1 533.7 99.2 96.3 93.1 88.9 Example 2 506.3 99.5 97.3 94.6 89.5 Example 3 529.5 99.3 95.8 93.7 88.1 Comparative Example 1 329.2 87.5 79.3 70.2 59.2 Comparative Example 2 293.8 99.3 96.5 79.4 68.8
[0073] From the above experimental data, it can be found that the capacity retention rate of Examples 1-3 is maintained at a high level at 100 weeks, 300 weeks, 600 weeks and 1000 weeks.
[0074] Compared with the embodiment, the initial capacity of Comparative Example 1 is lower than that of the embodiment. This is because zinc element is not doped into the graphite in its process steps, which makes it difficult for a cross-linked network to occur in the graphite, resulting in a reduced initial capacity. It can be found that its capacity retention rates at 100 weeks, 300 weeks, 600 weeks, and 1000 weeks are all lower than those of the embodiment, and the decrease is obvious, which is caused by changes in the internal structure of graphene.
[0075] The initial capacity of Comparative Example 2 is lower than that of Examples 1-3 and Comparative Example 1. This is because there is no tetraethyl orthosilicate involved in its process steps, resulting in the absence of silicon dioxide on the surface of the cross-linked network, and the battery capacity cannot be improved. The data in the 100-week and 300-week capacity retention rate tests are basically the same as those in the examples, but there is a cliff-like drop at 600 weeks. Analysis shows that there may be problems with the combination of the cross-linked structure and graphite, resulting in changes in the internal structure of the graphite, resulting in obvious capacitance attenuation.
[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a graphite negative electrode material, characterized in that: The steps include: Step 1, adding expanded graphite to a zinc chloride solution, and then adding sodium dodecylbenzene sulfonate, heating and stirring, after the stirring is completed, filtering the reaction mixture to separate the zinc-containing graphite material, washing and drying it for later use; Step 2: adding the zinc-containing graphite material obtained in step 1 to the phytic acid solution, heating and stirring, filtering the reacted material after stirring, separating the graphite solid, washing and drying the solid for later use; Step 3: Add the graphite solid obtained in step 2 to the ethyl orthosilicate solution, heat and stir, and after stirring, filter the reacted product to separate the solid product, wash and dry to obtain the graphite negative electrode material.
2. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: In step 1, the zinc chloride solution is prepared by mixing zinc chloride with deionized water to prepare a solution with a concentration of 0.1 to 1 mol / L; the mass ratio of expanded graphite to zinc chloride solution is 1:5 to 20; and sodium dodecylbenzene sulfonate is added according to 1% to 5% of the mass of the expanded graphite.
3. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: Step 1: Stirring with a magnetic stirrer; stirring temperature 40-80°C, stirring speed 200-500 rpm, stirring time 6-12h.
4. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: In step 2, the phytic acid solution is prepared by mixing phytic acid powder with deionized water to prepare a solution with a concentration of 0.5 to 0.8 mol / L; the mass ratio of the zinc-containing graphite material to the phytic acid solution is 1:40 to 50.
5. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: In step 2, a magnetic stirrer is used for stirring; the stirring temperature is 40-60° C., the stirring speed is 200-300 rpm, and the stirring time is 12-24 h.
6. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: In step 3, the ethyl orthosilicate solution is prepared by mixing ethyl orthosilicate and ethanol in a volume ratio of 1:3 to 5; the mass ratio of graphite solid to ethyl orthosilicate solution is 1:30 to 50.
7. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: In step 3, a magnetic stirrer is used for stirring; the stirring temperature is 30-50° C., the stirring speed is 300-350 rpm, and the stirring time is 6-8 h.
8. The method for preparing a graphite negative electrode material according to claim 1, characterized in that: In step 3, the solid product is washed with deionizer for 5 to 8 times; the drying temperature is 60 to 100° C. and the drying time is 2 to 4 hours.
9. A graphite negative electrode material, characterized in that: The graphite negative electrode material is prepared by the method for preparing the graphite negative electrode material according to any one of claims 1 to 8.
10. A battery, characterized in that: The negative electrode material is prepared by the method for preparing the graphite negative electrode material according to any one of claims 1 to 8.
Citation Information
Patent Citations
Method of preparing silicon-carbon composite lithium battery negative electrode material based on expanded graphite
CN107394158A
Graphene enhanced phytic acid-based passivator, preparation method and application
CN113265651A